The Pyramid of Injury: Estimation of the Scale of Adolescent Injuries According to Severity - Hyejin Han; Bomi Park; Bohyun Park; Namsoo Park; Ju Ok Park; Ki Ok Ahn; Yang Ju Tak; Hye Ah Lee; Hyesook Park (Korean Society for Preventive Medicine, 2018)
Objectives Due to their developmental characteristics, adolescents have a higher probability than other age groups of experiencing injuries caused by accidents, violence, and intentional self-harm. The severity and characteristics of injuries vary by the intentionality and mechanism of injury; therefore, there is a need for a national-level estimate of the scale and the severity of injuries in adolescents that takes these factors into account. Methods By using data from the Emergency Department-based Injury In-depth Surveillance Data, National Emergency Department Information System, the Korean National Hospital Discharge In-depth Injury Survey, and cause of death statistics, we calculated the emergency department (ED) visit rate, hospitalization rate, and death rate of injuries per 100 000 adolescents for each injury mechanism. The calculated rates were used to generate the injury pyramid ratio (ratio of death rate to hospitalization rate to ED visit rate) to visualize the scale and the severity of the injury. Results The mortality rate in adolescents due to injury was 10/100 000; the corresponding rates for hospitalization and ED visits were 1623 and 4923, respectively, resulting in an injury pyramid ratio with the general pyramid form, with a 1:162:492 ratio of deaths to hospitalizations to ED visits. The mortality rate due to suicide/intentional self-harm was 5/100 000, while 35 were hospitalized for this reason and 74 made ED visits. The pyramid ratio of 1:7:15 for intentional self-harm/suicide showed a steep pyramidal form, indicating considerable lethality. The mortality rate due to motor vehicle collisions (MVCs) was 3/100 000; 586 were hospitalized for this reason, while 1023 made ED visits. The pyramid ratio of 1:195:341 for MVCs showed a gradual pyramid form, indicating that the lethality was low and the scale of injury was high. Conclusions The main categories of injuries in adolescents were visualized in pyramid form, contributing to an understanding of the scale of each injury by mechanism in terms of levels of death, hospitalization, and ED visits. These findings will be helpful for understanding how to prioritize injuries in adolescents.